2018
DOI: 10.7717/peerj.5177
|View full text |Cite
|
Sign up to set email alerts
|

Assessing metacognitive beliefs about worry: validation of German versions of the Why Worry Scale II and the Consequences of Worry Scale

Abstract: BackgroundMetacognitive beliefs have been proposed to play a key role in initiating and maintaining worry. The Why Worry-Scale-II (WW-II) and Consequences of Worry Scale (COWS) are self-report questionnaires assessing positive and negative metacognitive beliefs. The main goal of this study was to validate German versions of these two questionnaires.MethodN = 603 participants completed a questionnaire battery, including the two self-report measures of metacognitive beliefs. We conducted confirmatory factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…As described in Table 1, all items loaded onto their factors consistent with findings from the Hebert et al (2014) and Thielsch et al (2018) nonclinical populations. Items that exceeded the criteria of loading at 0.40 or above were retained (i.e., all items).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…As described in Table 1, all items loaded onto their factors consistent with findings from the Hebert et al (2014) and Thielsch et al (2018) nonclinical populations. Items that exceeded the criteria of loading at 0.40 or above were retained (i.e., all items).…”
Section: Resultssupporting
confidence: 81%
“…Finally, we examined whether there are mean differences between groups with primary diagnoses of GAD, MDD or anxiety NOS using analysis of variance (ANOVA) and post hoc contrasts if indicated. 1, all items loaded onto their factors consistent with findings from the Hebert et al (2014) and Thielsch et al (2018) nonclinical populations. Items that exceeded the criteria of loading at 0.40 or above were retained (i.e., all items).…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…The research has revealed that there is a consistent and positive correlation between academic self-efficacy and many variables affecting students' academic achievement (Atoum & Al-Momani, 2018;Bahar, 2019;Camelo-Lavadores, Sánchez-Escobedo, & Pinto-Sosa, 2017;Dadandi, 2018;Doménech-Betoret, Abellán-Roselló, & Gómez-Artiga, 2017;Koca & Dadandi, 2019). Though there are studies separately investigating the concepts of academic self-efficacy (Aslan & Agiroglu-Bakir, 2017;Cava-Kuru, 2018;Grøtan, Sund, & Bjerkeset, 2019;Korucu & Cinar, 2017;Makhabbat, Coklar, & Gunduz, 2018;Qamar, Parveen, & Yousuf, 2017;Sachitra & Bandara, 2017;Sokmen, 2018;Sula-Atas & Kumcagiz, 2019;Verešová & Foglová, 2017;Ye, Posada, & Liu, 2018), intolerance of uncertainty (Buhr & Dugas, 2002;Coskun, 2017;Freeston, Rhéaume, Letarte, Dugas, & Ladouceur, 1994;Ranney, Behar, & Bartoszek, 2019;Stanley-Budner, 1962;Sirin-Ayva, 2018;Yildiz, 2017), positive beliefs about worry (Borkovec et al, 1999;Gosselin et al, 2003;Goc, 2017;Karatas & Uzun, 2018;Penney, Mazmanian, & Rudanycz, 2013;Thielsch, Andor, & Ehring, 2018) and academic locus of control (Akin, 2007;Certel & Kozak, 2017;Celik & Saricam, 2018;Cok, 2018;D...…”
Section: Importance Of Researchmentioning
confidence: 99%